Learning Model Halfway House in Shaping Social Behavior - I Nyoman Wijana; Suryadi Suryadi; Syahrir Ibnu (ijd-demos, 2022)
AbstractThis study aims to determine how the Harley Davidson Club Indonesia Rabbani Halfway House’s learning model is to know how social behavior is and how the Harley Davidson Club Indonesia Rabbani Halfway House learning model shapes children’s social behavior. This research uses a qualitative approach with a type of case study. Collecting data using observation, interview and documentation techniques. The subjects of this research include supervisors, teachers, volunteers, and students involved in the learning process. The learning model here is how the Rumah Singgah learning system shapes children’s social behavior. Social behavior itself can be said to how a person responds to others. Or perform a conscious behavior. Shaping this behavior is the main task of parents because there are children who have limitations such as incomplete families and economic factors, so the Halfway House was established. Based on the results of data analysis, there are several essential things in the learning model of the Harley Davidson Club Indonesia Insan Rabbani Halfway House in shaping children’s social behavior, namely: 1) instilling Islamic values, 2) involving students, 3) self-development through extracurricular activities, 4) providing guidance and directions for parents, 5) foster parents and a supportive environment is needed for the development of children to have good social behavior.Keywords: Learning Model, Halfway House, Social Behavior. AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana model pembelajaran Rumah Singgah Harley Davidson Club Indonesia Rabbani untuk mengetahui bagaimana perilaku sosial dan bagaimana model pembelajaran Rumah Singgah Harley Davidson Club Indonesia Rabbani membentuk perilaku sosial anak. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi. Subyek penelitian ini meliputi pengawas, guru, relawan, dan siswa yang terlibat dalam proses pembelajaran. Model pembelajaran disini adalah bagaimana sistem pembelajaran Rumah Singgah membentuk perilaku sosial anak. Perilaku sosial itu sendiri dapat dikatakan bagaimana seseorang menanggapi orang lain. Atau melakukan perilaku sadar. Membentuk perilaku ini menjadi tugas utama orang tua karena ada anak yang memiliki keterbatasan seperti keluarga yang tidak lengkap dan faktor ekonomi, maka didirikanlah Rumah Singgah. Berdasarkan hasil analisis data, ada beberapa hal yang esensial dalam model pembelajaran Harley Davidson Club Indonesia Insan Rabbani Halfway House dalam membentuk perilaku sosial anak, yaitu: 1) menanamkan nilai-nilai Islam, 2) melibatkan siswa, 3) kemandirian. pengembangan melalui kegiatan ekstrakurikuler, 4) memberikan bimbingan dan arahan kepada orang tua, 5) orang tua asuh dan lingkungan yang mendukung diperlukan bagi perkembangan anak agar memiliki perilaku sosial yang baik.Kata kunci: Model Pembelajaran, Rumah Singgah, Perilaku Sosial